Determinants of Sovereign Rating: Factor Based Ordered Probit Models for Panel Data Analysis Modeling Framework - Teker, Dilek; Pala, Aynur; Kent, Oya (International Journal of Economics and Financial Issues, 2012)
The aim of this research is to compose a new rating methodology and provide credit notches to 23 countries which of 13 are developed and 10 are emerging. There are various literature that explains the determinants of credit ratings. Following the literature, we select 11 variables for our model which of 5 are eliminated by the factor analysis. We use specific dummies to investigate the structural breaks in time and cross section such as pre crises, post crises, BRIC membership, EU membership, OPEC membership, shipbuilder country and platinum reserved country. Then we run an ordered probit model and give credit notches to the countries. We use FITCH ratings as benchmark. Thus, at the end we compare the notches of FITCH with the ones we derive out of our estimated model. Keywords: Credit notches; factor analysis; ordered probit model JEL Classifications: G01; G23